Uncertainty on w from large-scale structure - Marra, Valerio; Pääkkönen, Mikko; Valkenburg, Wessel (Monthly notices of the Royal Astronomical Society, 2013)
We find that if we live at the centre of an inhomogeneity with total density contrast |δ0| ≃ 0.1-0.15, dark energy is not a cosmological constant at 95 per cent confidence level. Observational constraints on the equation of state of dark energy, w, depend strongly on the local matter density around the observer. We model the local inhomogeneity with an exact spherically symmetric solution which features a pressureless matter component and a dark-energy fluid with constant equation of state and negligible sound speed, which reaches a homogeneous solution at finite radius. We fit this model to observations of the local expansion rate, distant supernovae and the cosmic microwave background. We conclude that the possible uncertainty from large-scale structure has to be taken into account if one wants to progress towards not just precision but also accurate cosmology.